2015
DOI: 10.1038/srep11037
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary History of R2R3-MYB Proteins Across 50 Eukaryotes: New Insights Into Subfamily Classification and Expansion

Abstract: R2R3-MYB proteins (2R-MYBs) are one of the main transcription factor families in higher plants. Since the evolutionary history of this gene family across the eukaryotic kingdom remains unknown, we performed a comparative analysis of 2R-MYBs from 50 major eukaryotic lineages, with particular emphasis on land plants. A total of 1548 candidates were identified among diverse taxonomic groups, which allowed for an updated classification of 73 highly conserved subfamilies, including many newly identified subfamilies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(186 citation statements)
references
References 58 publications
14
156
1
Order By: Relevance
“…The MYB genes identified in this network belong to the R2R3-MYB family. The R2R3-MYB family has undergone expansion in plants (Du et al 2014) and plays many important plant-specific roles. Furthermore, there are many kinase and phosphatase related genes in close association with genes responsible for phosphorylation and dephosphorylation of splicing regulators, such as serine-threonine protein kinase (CIPK3), calcium-dependent protein kinase 29 (CPK29), CBL-interacting protein kinase 9 (CIPK9), and calcineurin b-like protein (CBL1).…”
Section: Resultsmentioning
confidence: 99%
“…The MYB genes identified in this network belong to the R2R3-MYB family. The R2R3-MYB family has undergone expansion in plants (Du et al 2014) and plays many important plant-specific roles. Furthermore, there are many kinase and phosphatase related genes in close association with genes responsible for phosphorylation and dephosphorylation of splicing regulators, such as serine-threonine protein kinase (CIPK3), calcium-dependent protein kinase 29 (CPK29), CBL-interacting protein kinase 9 (CIPK9), and calcineurin b-like protein (CBL1).…”
Section: Resultsmentioning
confidence: 99%
“…For the residues within the MYB domain identified as differing between SG6 and the other subgroups (Schwinn et al ., ), in most cases Mp MYB02 and Mp MYB14 are more closely aligned to SG5/7 and not SG6. This is supported by the phylogenetics, as no SG6 sequences have been identified from nonangiosperm species (Du et al ., ; and Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is tempting to speculate that the evolution of the WER/MYB23 genes was the critical factor in the origin of the Arabidopsis type 3 pattern. However, a recent extensive analysis of MYB genes in multiple species showed that subgroup 15 includes members from several type 1 eudicots (Du et al, 2015), complicating the potential linkage between this subgroup and the type 3 pattern. Interestingly, the patterning of epidermal hairs (trichomes) on the leaf surface of Arabidopsis also relies on a member of this MYB subgroup 15, the GL1 gene (Larkin et al, 1993), implying shared evolution of these patterning mechanisms.…”
Section: Discussionmentioning
confidence: 99%